Analisis Pengaruh Variabel Demografis Terhadap Minat Beli Jajanan Tradisional di Kecamatan Kraton Yogyakarta - Muhammad Khairullah (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2020)
The snacks' traditional ancestral heritage from an ancient tradition that has value in the culture of Indonesia. The era of globalization affects a person's lifestyle so that the public will follow the trend of including in the Affairs of food. With a large number of diverse snacks food immediacy from abroad with all the innovation sense and shape, making it increasingly attractive to the present traditional society and leave traditional snacks in history. This research aims to know the relationship of demographic variables against the interest in buying traditional snacks in the district of Yogyakarta Kingdom. These studies use quantitative methods in which data collection is done by a questionnaire and interviews to all walks of life in the district of Kraton Yogyakarta so that it is able to multiply and analyze information more deeply about the relationship demographic variables of interest to buy against traditional snacks. The demographic variables used in this research are gender, age, level of education, occupation, income, lifestyle, and cultural reference groups. In General, the results of the study indicate that there is a relationship between variables – variables demographics towards an interest in buying the traditional snacks in the district of Yogyakarta Kingdom. Specifically, the variables have a relationship are variable is the work while the variable gender, the variables age, the variable education level, the variable income, the variable lifestyle, the variables reference groups and the variable cultural have weak relationships with interest to buy traditional snacks in the district of Yogyakarta Kingdom